2008
DOI: 10.1053/j.gastro.2008.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Hedgehog-Responsive Progenitors Parallels Alcoholic Liver Disease Severity in Mice and Humans

Abstract: Background & Aims-Improving outcomes in alcoholic liver disease (ALD) necessitates better understanding of how habitual ethanol (EtOH) consumption alters normal regenerative mechanisms within the liver. Hedgehog (Hh) pathway activation promotes expansion of progenitor populations in other tissues. We evaluated the hypothesis that chronic EtOH exposure activates Hh signaling in liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 53 publications
10
123
0
2
Order By: Relevance
“…Other studies from the same and other research groups described morphological evidence for EMT of BDEC also in liver biopsies from human patients affected by primary sclerosing cholangitis (PSC, Kirby et al, 2008), primary biliary cirrhosis (PBC, Jung et al, 2007;Robertson et al, 2007;Omenetti et al, 2008b) or biliary atresia (Diaz et al, 2008). Similar evidence has been reported EMT of BDEC in post-transplantation recurrence of PBC (Robertson et al, 2007) and the relevance of Hedgehog and TGF 1-Smad2/3 signalling was reported also in human patients (Jung et al, 2007(Jung et al, , 2008Omenetti et al, 2008b;Robertson et al, 2007;Rygiel et al, 2008).…”
Section: Hepatocytes or Cholangiocytes Are An Unlikely Sources Of Mfssupporting
confidence: 84%
See 1 more Smart Citation
“…Other studies from the same and other research groups described morphological evidence for EMT of BDEC also in liver biopsies from human patients affected by primary sclerosing cholangitis (PSC, Kirby et al, 2008), primary biliary cirrhosis (PBC, Jung et al, 2007;Robertson et al, 2007;Omenetti et al, 2008b) or biliary atresia (Diaz et al, 2008). Similar evidence has been reported EMT of BDEC in post-transplantation recurrence of PBC (Robertson et al, 2007) and the relevance of Hedgehog and TGF 1-Smad2/3 signalling was reported also in human patients (Jung et al, 2007(Jung et al, , 2008Omenetti et al, 2008b;Robertson et al, 2007;Rygiel et al, 2008).…”
Section: Hepatocytes or Cholangiocytes Are An Unlikely Sources Of Mfssupporting
confidence: 84%
“…One should consider the following facts and hypothesis: a) neoplastic cells may be envisaged to derive either from hepatic progenitor cells (HPCs) or adult and DNA-damaged hepatocytes being sustained by paracrine or survival factors released by MFs or directly from HSC/MFs through a process of mesenchymal to epithelial transition into HPCs; the latter hypothesis is highly speculative, but supported by the notion that in HSC/MFs operate hedgehog and Wnt signalling, two pathways that have been implicated in stem cell differentiation and cancer. Another study went further in proposing an even more speculative and fascinating scenario (Yang et al, 2008) in which HSC may represent a type of oval cell thus being potentially able to generate hepatocytes to repopulate injured livers. In this elegant study, since quiescent HSC express glial fibrillary acidic protein (GFAP), mice in which GFAP promoter elements regulated Cre-recombinase were crossed with ROSA-loxP-stop-loxP-green fluorescent protein (GFP) mice to generate GFAP-Cre/GFP double-transgenic mice.…”
Section: Hsc/mfs and Their Putative Role In Liver Regeneration And Camentioning
confidence: 99%
“…Hence, when TGF-β is present, canonical Hh pathway activation stimulates expression of factors that promote EMT by downregulating the epithelial adhesion molecule E-cadherin (69,70). Recently, we reported that TGF-β1 treatment induces expression of Hh ligands in liver cells (71), identifying a mechanism that helps to explain why both factors accumulate during liver fibrosis. TGF-β has also been shown to induce EMT via noncanonical (i.e., Hh ligand-independent) activation of Gli transcription factors (72).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of infant fibrosis (biliary atresia, Caroli's disease, congenital hepatic fibrosis) and adult primary biliary cirrhosis (PBC), primary sclerosing cholangitis (PSC), and secondary biliary fibrosis, all liver diseases of other etiologies, once advanced, develop into a portal fibrosis with proliferation of biliary progenitors, especially when excessive hepatocyte apoptosis forces the stem cell niche to produce biliary progenitors. These biliary progenitors are more resistant to enhanced oxidative stress and hepatocyte death, such as induced by ASH, NASH, or severe post-transplant hepatitis C (55)(56)(57)(58)(59)(60). Drugs aimed at the biliary fibrogenic progenitors are effective antifibrotic agents in rodent biliary and advanced non-biliary fibrosis.…”
Section: Figurementioning
confidence: 99%